Methodologies in architectural research - Hj Mohd Ariffin, Noor Aziah (IIUM Press, 2015)
This book is intended to appeal to people interested in doing research in architecture and the built environment Being both comprehensive and could act as an entry level point into the world of research in architecture, this book targets primarily, final year undergraduate and post graduate students and anybody interested in doing research in these field. Through the topics covered in the book varied methods researches were introduced to, perhaps, whet the interests of budding researchers as how to conduct their impending issues and questions yet unanswered. Although the topics covered are not as varied but it would serve as a guide to construct and undertake a research project as offered by the authors in answering their research question.